(untitled) (International Journal of Physiology, 2019)
Cigarette and Bidi smoking are quite common in Uttar Pradesh. The present study was conducted in Muzaffarnagar city of Western Uttar Pradesh to assess the cardiovascular status of young male chronic smokers by estimating their hsCRP and lipid levels. A total of 100 subjects divided into two groups of control and smokers having a chronic history of smoking were taken for the study. Proper exclusion criteria were applied to the case selection. After applying the standard stastical tests we found that dyslipdemia and hsCRP level significantly increased (p<.05)* in smokers(2.72+2.02)* as compared to normal population(1.13+1.07). So we can confer these smokers with higher hs CRP levels and dyslipidemias are at higher risk of CADs in future.